What drives patentees to bypass TTOs? Evidence from a large PRO - Rajeev K. Goel; Devrim Göktepe-Hultén (Kiel Institute for the World Economy (IfW), 2017)
This paper provides insights into the behavior of academic patentees who choose to bypass in-house Technology Transfer Offices (TTOs). TTOs have gained favor in recent years as academic institutions have tried to increase commercialization of their inventions. Using a large sample of researchers at a leading German Public Research Organisation (PRO), results show that patentees in physical and life sciences, those with doctoral degrees, and those with greater job experience are more likely to bypass TTOs. Different forms of industry interactions, including working in industry, industry cooperation and industry consulting, all make TTO-bypassing more likely, with some interesting differences across gender. On the other hand, internal leadership position as a research group leader, German citizenship and risk attitudes do no exert significant influences on the propensity to bypass TTOs.
Keywords: O31; O34; D23; D83; 330; patents; Technology Transfer Office (TTO); Public Research Organisation (PRO); industry interactions; gender; Germany